JAK1 is a novel target of tumor- and invasion-suppressive microRNA 494-5p in colorectal cancer - Patil, Nitin; Abdelrahim, Omar Gamal; Leupold, Jörg; Allgayer, Heike (Cancers, 2024)
MiR-494-5p expression has been suggested to be associated with colorectal cancer (CRC) and its metastases in our previous studies. However, functional investigations on the molecule-mediating actions of this miR in CRC are lacking. In silico analysis in the present study revealed a putative binding sequence within the 3′UTR of JAK1. Overexpression of miR-494-5p in cultured CRC significantly reduced the luciferase activity of a reporter plasmid containing the wild-type JAK1-3′UTR, which was abolished by seed sequence mutation. Furthermore, the overexpression of miR-494-5p in CRC cell lines led to a significant reduction in JAK1 expression, proliferation, in vitro migration, and invasion. These effects were abolished by co-transfection with a specific double-stranded RNA that inhibits endogenous miR-494-5p. Moreover, IL-4-induced migration, invasion, and phosphorylation of JAK1, STAT6, and AKT proteins were reduced after an overexpression of this miR, suggesting that this miR affects one of the most essential pathways in CRC. A Kaplan-Meier plotter analysis revealed that patients with high JAK1 expression show reduced survival. Together, these data suggest that miR-494-5p physically inhibits the expression of JAK1 at the translational level as well as in migration and invasion, supporting the hypothesis of miR-494-5p as an early tumor suppressor and inhibitor of early steps of metastasis in CRC.